Variable returns to fertilizer use and its relationship to poverty: Experimental and simulation evidence from Malawi - Harou, Aurélie; Liu, Yanyan; Barrett, Christopher B.; You, Liangzhi (International Food Policy Research Institute, 2014)
Despite the rise of targeted input subsidy programs in Africa over the last decade, several questions remain as to whether low and variable soil fertility, frequent drought, and high fertilizer prices render fertilizer unprofitable for large subpopulations of African farmers. To examine these questions, we use large-scale, panel experimental data from maize field trials throughout Malawi to estimate the expected physical returns to fertilizer use conditional on a range of agronomic factors and weather conditions. Using these estimated returns and historical price and weather data, we simulate the expected profitability of fertilizer application over space and time. We find that the fertilizer bundles distributed under Malawi’s subsidy program are almost always profitable in expectation, although our results may be reasonably interpreted as upper-bound estimates among more skilled farmers given that the experimental subjects were not randomly selected.